2019
DOI: 10.15446/rev.colomb.biote.v21n2.69421
|View full text |Cite
|
Sign up to set email alerts
|

Identificación de Bacillus toyonensis en heces de ganado cebú en el Departamento de Sucre, Colombia

Abstract: Se evaluaron las características probióticas de cepas nativas aisladas de ganado cebú y se realizó identificación molecular de una de estas cepas, para considerar su posterior aplicación como aditivos microbianos en la alimentación bovina. Se usaron muestras de estiércol de terneros de levante, se aislaron bacterias y levaduras, determinándose la capacidad probiótica de estas cepas mediante pruebas como; resistencia a sales biliares (0.05, 0.1, 0.15 y 0.3 %), resistencia a pH ácido (pH 3, 4, 5.6, 7), toleranci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
2
2
0
1
Order By: Relevance
“…In particular, the physiological pH range in the rumen has been reported to be between 5.5 and 6.9 (Choudhury et al, 2015). In keeping with this, all the BC we evaluated in MNA broth had the optimum development at a similar pH range of 6.5 and 7 at 24 and 48 h. This same pattern was also found in other works in which the highest bacterial growth was shown to occur at pH close to 7 with a significant decrease at acidic pH (Ávila et al, 2010;Bertel et al, 2019;Castillo et al, 2018 andLanda-Salgado et al, 2019). Moreover, Marrero et al (2010) evaluated different strains of bacilli and reported high growth of cellulolytic bacteria at pH at the rumen level of 6.6.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In particular, the physiological pH range in the rumen has been reported to be between 5.5 and 6.9 (Choudhury et al, 2015). In keeping with this, all the BC we evaluated in MNA broth had the optimum development at a similar pH range of 6.5 and 7 at 24 and 48 h. This same pattern was also found in other works in which the highest bacterial growth was shown to occur at pH close to 7 with a significant decrease at acidic pH (Ávila et al, 2010;Bertel et al, 2019;Castillo et al, 2018 andLanda-Salgado et al, 2019). Moreover, Marrero et al (2010) evaluated different strains of bacilli and reported high growth of cellulolytic bacteria at pH at the rumen level of 6.6.…”
Section: Discussionsupporting
confidence: 88%
“…Finally, the relative species abundance based on DNA sequences of potential probiotic BC showed that all of those cultured in MRS belong to the phylum Firmicutes and all of them to the class Bacilli , whereas the BC cultured in MNA broth belong mainly to the phylum Proteobacteria (class Grammaproteobacteria ) (data not shown). Castillo et al (2018) and Bertel et al (2019), as in our study, identified Enterococcus and Bacillus in samples with the best results in the probiotic tests. Zhou et al (2015) found that in ruminal populations the most abundant phyla always fell on Firmicutes and Bacteroidetes .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Se requiere tolerancia a las sales biliares para que las levaduras sobrevivan en el intestino delgado durante su paso por el tracto gastrointestinal. La concentración óptima de bilis del intestino humano y rumiantes oscila entre 0,3 y 0,6 %; esta es importante para su buen funcionamiento, lo que permite mejorar su actividad y la digestibilidad de los nutrientes (Bertel et al, 2019;Helmy et al, 2019). Por consiguiente, evaluar la resistencia a este tipo de sales que se encuentran en el tracto gastrointestinal es un factor relevante para seleccionar levaduras con potenciales propiedades probióticas.…”
Section: Capacidad Probiótica De Las Levaduras Mediante Ensayos In Vitrounclassified